REINSTRUMENTASI FUNGSI ZAKAT MENUJU PENGENTASAN KESENJANGAN SOSIAL EKONOMI UMAT - Juhari - (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2010)
Zakat is a worship mâliyah ijtimâ’iyah that has very importantand strategic position in empowering and development ofeconomic welfare in society. Because of that, zakat can functionas an instrument of even distribution of society’s economy. Butthis function is not longer felt by the society because of somereasons. The first, the knowledge of society to their treasure thatzakat must be given is limited to the konventional sources. Thesecond, the mechanism of zakat distribution is still traditionalkonsumptif. In such a way, the function of instrumentatif zakatas a media of mental learning mustahiq to put productive wayforward in financing is not reached. Therefore, theunderstanding of society. management and its distributionneed refreshing. This writing discusses how zakat can reallyfunction as the solution of imbalance society’s economy.